Hydrogel technologies in andrology: advances in research and prospective applications - Guo, Xinlei; Zhang, Jingyi; Guan, Yanxin; Tian, Xingzhao; Gong, Yanan; Xiao, Yao; Yang, Fang; Chang, Degui; Yu, Xujun (Frontiers in Pharmacology, 2025)
Hydrogels, owing to their outstanding physicochemical properties and excellent biocompatibility, have emerged as a focal point of research and clinical application in andrological diseases. This review systematically summarizes cutting-edge progress in hydrogel applications for Prostate Cancer (PC), Bladder Cancer (BC), Erectile Dysfunction (ED), Male Reproductive Medicine (MRM), and urinary tract tissue engineering. Current studies indicate that hydrogels can serve as protective spacers in PC radiotherapy to mitigate radiation-induced rectal toxicity and as precise drug-delivery vehicles to enhance antitumor efficacy. Moreover, hydrogels demonstrate unique and broad potential in neurovascular repair, immunomodulation, sperm selection, in vitro spermatogenesis modeling, and tissue regeneration. Future advancements in hydrogel technology—through intelligent responsive design, integration of bioactive molecules, incorporation of advanced manufacturing processes, and rigorous translational research—are expected to significantly elevate treatment standards for andrological diseases and improve patient quality of life.